KATEGORI TUMBUH-TUMBUHAN WIT DAN SUKET DALAM BAHASA JAWA - . Suhandano (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
Javanese speakers classify plants into two major categories which are named by the words of wit and suket in their language. Generally the word wit reffers to large plants while the word suket refers to small plants. However, the size of plants is not the only criterion; there are some small plants which are referred to as wit not suket. In this case, it seems that the function of plants in Javanese society is also another criterion and there are cultural reasons why such plants are classified as wit.